200k views
1 vote
3x -10+ 4x= -2 (x-4) +9

User Yachi
by
4.7k points

2 Answers

1 vote
The answer is

7x-10=-2x+8+9
7x-10=-2x+17
7x+2x=17+10
9x=27
x=3
User Cgiacomi
by
4.9k points
3 votes

Answer:

x = 3

Explanation:

Step 1: Write equation

3x - 10 + 4x = -2(x - 4) + 9

Step 2: Solve for x

  1. Distribute -2: 3x - 10 + 4x = -2x + 8 + 9
  2. Combine like terms: 7x - 10 = -2x + 17
  3. Add 2x to both sides: 9x - 10 = 17
  4. Add 10 to both sides: 9x = 27
  5. Divide both sides by 9: x = 3

Step 3: Check

Plug in x to verify it's a solution.

3(3) - 10 + 4(3) = -2(3 - 4) + 9

9 - 10 + 12 = -2(-1) + 9

-1 + 12 = 2 + 9

11 = 11

User Sigroad
by
5.1k points